2015
DOI: 10.1055/s-0035-1546173
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Compounds as Pancreatic Lipase Inhibitors

Abstract: Obesity and its associated diseases such as diabetes mellitus and coronary heart diseases are a major challenge for our society. An important target for the treatment of obesity includes the development of inhibitors of nutrient digestion and absorption. Inhibition of pancreatic lipase and the associated reduction of lipid absorption is an attractive approach for the discovery of potent agents. Currently, the only clinically approved pharmacologic agent as pancreatic lipase inhibitor is Orlistat. However, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
175
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(186 citation statements)
references
References 73 publications
6
175
0
5
Order By: Relevance
“…The importance of polyphenolic substances as potential inhibitors of PL were discussed recently by Buchholz and Melzig. [31] Several flavonoids, as the largest class of polyphenolic substances, have been evaluated and the studies indicated that the flavonoids having hydroxyl or methoxy groups at C3’ and C4’ in ring B as well as C-glycosidic flavones favor the PL inhibition. [313233] Additionally, the efficacy of phenolic acids, namely caffeic-, rosmarinic-, and ferulic acids, as PL inhibitors are well described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of polyphenolic substances as potential inhibitors of PL were discussed recently by Buchholz and Melzig. [31] Several flavonoids, as the largest class of polyphenolic substances, have been evaluated and the studies indicated that the flavonoids having hydroxyl or methoxy groups at C3’ and C4’ in ring B as well as C-glycosidic flavones favor the PL inhibition. [313233] Additionally, the efficacy of phenolic acids, namely caffeic-, rosmarinic-, and ferulic acids, as PL inhibitors are well described.…”
Section: Resultsmentioning
confidence: 99%
“…[31] Several flavonoids, as the largest class of polyphenolic substances, have been evaluated and the studies indicated that the flavonoids having hydroxyl or methoxy groups at C3’ and C4’ in ring B as well as C-glycosidic flavones favor the PL inhibition. [313233] Additionally, the efficacy of phenolic acids, namely caffeic-, rosmarinic-, and ferulic acids, as PL inhibitors are well described. [3435] In effect, the results of the present study indicate that the PL inhibitory efficacy of A. hygrophilum may be attributable to their multiple phenolic components acting additively or synergistically.…”
Section: Resultsmentioning
confidence: 99%
“…56,57 As a natural triterpenoid widely found in several dietary and medicinal plants (e.g., Olea europaea, Viscum album L., or Aralia chinensis L.), OA has been used in Chinese medicine for the treatment of liver disorders for over 20 years, and commercial OA tablets are available as OTC drugs in Chinese pharmacies for the treatment of acute and chronic hepatitis infections. 30,58 Although they are slow-acting, herbal medicines and medical nutrition therapies are recommended for liver disease patients over pharmacotherapies that utilize chemically synthesized drugs, because the former elicit milder metabolic burdens on a defective liver during the unavoidable hepatic first pass of xenobiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Tina Buchholz, Matthias F. Melzig [21] Obesity and its associated diseases such as diabetes mellitus and coronary heart diseases are a major challenge for our society. Billington CJ, Epstein LH [22] More than half of adult Americans are overweight or obese, and public health recommendations call for weight loss in those who are overweight with associated medical conditions or who are obese.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%